The impact of financial ratios on bank profitability: evidence from idx (2021-2023) - Sari, Karima; Fauzan , Fauzan (Law and Economics, 2025)
: This study examines the impact of Non-Performing Loans (NPL), the Operating Expenses to Operating Income Ratio (BOPO), Net Interest Margin (NIM), Loan to Deposit Ratio (LDR), and Capital Adequacy Ratio (CAR) on Return on Assets (ROA) in banking institutions listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. Employing a quantitative research methodology, this study utilizes purposive sampling to select banks based on operational status and financial performance, with secondary data sourced from annual reports and financial statements. The research applies multiple regression analysis to examine relationships between variables, alongside classical assumption tests to ensure model validity. The findings reveal that NPL and BOPO have a significant negative effect on ROA, indicating that higher NPL increases credit risk and reduces profitability, while inefficient operations lower financial performance. Conversely, NIM positively and significantly affects ROA, suggesting that higher NIM enhances earnings from productive assets. However, LDR and CAR do not exhibit a significant impact, implying that credit distribution and capital adequacy do not directly influence profitability. Given these findings, future research should incorporate additional factors such as managerial efficiency, capital structure, and macroeconomic conditions while adopting qualitative approaches for deeper insights. For the banking sector, enhancing credit risk management, improving operational efficiency, and optimizing NIM are critical for sustained profitability. This study provides valuable insights for banking stakeholders and serves as a reference for further research on profitability determinants in the banking industry.